Incorporation as Unification - Bende-Farkas, Ágnes (Proceedings of the Amsterdam Colloquium, 1999)
This paper proposes an analysis of a particular Definiteness Effect construction, that involving the light verb have as found in e.g. John has a sister. The analysis is based on the notion of term unification, which has played an important role in computer science and computational linguistics but, to my knowledge, hardly within formal semantics. According to term unification, the verb have and its object phrase both introduce a predicational "term" consisting of a predicate and its arguments. Combining verb and object phrase involves unifying these two terms. When unification fails for some reason, the combination is unacceptable. The analysis is capable of extension to other Definitesness Effect constructions, including thoses involving "light" verbs in Hungarian.